Faktor Yang Memengaruhi Perilaku Ibu Terhadap Pemberian Imunisasi Dasar Pada Bayi Di Desa Situmbaga Kecamatan Halongonan Timur Kabupaten Padang Lawas Utara - Evi Dayanti Harahap (Jurnal Komunitas Kesehatan Masyarakat, 2020)
The main obstacle to the success of the immunization program for infants is the low awareness of mothers who have babies to carry their children on immunizations. This type of research is an analytical survey method with cross sectional approach with the aim to determine the factors that influence maternal behavior towards basic immunization for infants with a population of all mothers who have babies as many as 66 people with a sample of the entire population. The results showed that knowledge had a sig-p value of 0.008 <0.05, a sig-p attitude of 0.005 <0.05, a sig-p confidence of 0.040 <0.05, the role of a sig-p health care provider of 0.046 <0.05 and a family support sig-p -p 0.004 <0.05. For work variables sig-p value 0.386> 0.05 and location / distance sig-p 0.900> 0.05. The conclusion is the influence of knowledge, attitudes, beliefs, the role of health workers and family support for basic immunization, while work and location / distance do not have an influence on basic immunization. It is hoped that this will be used as information material for health workers to be able to find out about ways to increase the insight of mothers to be able to provide basic immunizations to their babies.